Offence and morality: Pragmatic perspectives. (November 2022) - Haugh, Michael; Kádár, Dániel Z.; Márquez Reiter, Rosina
Abstract: Various scholars have studied the increasing occurrence of toxic, often large-scale arguments over allegedly offensive behaviour in both public and private discourse arenas. However, what is meant by offence itself is rarely discussed at length in linguistics and communication studies, and little systematic work has been dedicated to how offence is taken and reported on across different contexts and in different modes of communication. The aims of this special issue are to examine how interactants and observers of interaction take offence across different communicative settings and sociocultural contexts, to consider the moral and relational implications of taking or reporting offence, and to highlight what a pragmatics-based perspective can add to research on offence and its relationship with morality. Highlights: Shows how people take offence across different settings and sociocultural contexts. Examines the moral and relational implications of taking offence. Scrutinises the relationship between offence and morality. Discusses what a pragmatics perspective brings to research on offence.